Seq-ing Higher Ground: Functional Investigation of Adaptive Variation Associated With High-Altitude Adaptation - Hall, James E.; Lawrence, Elijah S.; Simonson, Tatum S.; Fox, Keolu (Frontiers in Genetics, 2020)
Human populations at high altitude exhibit both unique physiological responses and strong genetic signatures of selection thought to compensate for the decreased availability of oxygen in each breath of air. With the increased availability of genomic information from Tibetans, Andeans, and Ethiopians, much progress has been made to elucidate genetic adaptations to chronic hypoxia that have occurred throughout hundreds of generations in these populations. In this perspectives piece, we discuss specific hypoxia-pathway variants that have been identified in high-altitude populations and methods for functional investigation, which may be used to determine the underlying causal factors that afford adaptation to high altitude.